Beating Eating Disorders Step by Step : a Self-Help Guide for Recovery. - Paterson, Anna, 1968- (Jessica Kingsley Publishers, 2008)
People living with eating disorders find it hard to take the step of choosing recovery, often because the disorder has developed as a way of 'coping' with problems or stresses in the their life. This book outlines new and positive ways of dealing with eating disorders for people living with eating disorders and their families. A practical workbook written by someone who has lived with eating disorder, it provides advice and strategies to aid understanding and to help the reader to gain control of their illness. Anna Paterson leads the reader through easy-to-use therapeutic exercises, such as d.